2013
DOI: 10.1093/jat/bkt010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Ricin Biomarker, Ricinine, in 989 Individual Human Urine Samples

Abstract: Ricinine (3-cyano-4-methoxy-N-methyl-2-pyridone) is a urinary biomarker that can be measured to confirm human exposure to castor bean products such as ricin. Because many consumer products contain castor oil, another castor bean product, ricinine may be detectable in the general population. The following study characterized urinary ricinine concentrations from 989 individuals who were presumed to be unexposed to ricin. An automated diagnostic method was utilized to simplify the analysis of this large sample se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Ricinine may only serve as a surrogate marker or indicator of ricin intoxication, as the ricin toxin is not actually being detected. Additionally, ricinine is expected to be present in the general population, with a recovery rate of 1.2% in persons who were not suspected of ricin exposure . Currently, there are no reports of human ricinine poisonings.…”
mentioning
confidence: 99%
“…Ricinine may only serve as a surrogate marker or indicator of ricin intoxication, as the ricin toxin is not actually being detected. Additionally, ricinine is expected to be present in the general population, with a recovery rate of 1.2% in persons who were not suspected of ricin exposure . Currently, there are no reports of human ricinine poisonings.…”
mentioning
confidence: 99%
“…This is due to the presence of ricinine in pharmaceutical and cosmetic products containing castor oil (27). In a previous study, a larger convenience set of 989 individual urine specimens was analyzed, and ricinine was present in 1.2% of the specimens (28). The LRL for ricinine in urine and serum was determined to be fit-for-purpose at 0.300 ng/mL based on observations in unexposed convenience sets, animal studies, and previously reported exposures (1317, 28).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, a larger convenience set of 989 individual urine specimens was analyzed, and ricinine was present in 1.2% of the specimens (28). The LRL for ricinine in urine and serum was determined to be fit-for-purpose at 0.300 ng/mL based on observations in unexposed convenience sets, animal studies, and previously reported exposures (1317, 28). Example chromatograms of ricinine in a representative convenience set sample as compared to the LRL are plotted in Figure 3A.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, however, ricinine may also be detectable in the general population since many consumer products contain castor oil. This has been shown, for example, in a study of Pittman and co-workers who characterized urinary ricinine concentrations from 989 individuals presumably unexposed to ricin (Pittman et al 2013).…”
Section: Ricin Detectionmentioning
confidence: 89%